CONCEPTUAL CONTENT OF SILENCE IN THE HERITAGE OF THINKERS AND PROVERBS - Sobirova Feruza Asqarali qizi (Modern American Journals, 2025)
The article examines the socio-linguistic and communicative aspects of silence. Based on proverbs, literary sources, and thinkers’ views, its multiple meanings are revealed. Silence is interpreted as a nonverbal unit of communication with cultural and spiritual significance.
Keywords: Silence, communication, nonverbal unit, proverbs, intercultural communication